Study Of Protein Oxidation And Antioxidants Status In Pulmonary Tuberculosis Patients - RAMESH,; SUDHA K,; AMARESHWARA M,; SAMEER,; RAKESH M, (International Journal of Pharma and Bio Sciences, 2011)
Imbalance in the oxidants and antioxidant status indicates on going oxidative stress is considered as one of the etiological factor for development of lung function abnormalities. However no study has been performed to assess the oxidative stress in pulmonary tuberculosis. That’s why this study was over taken. Protein Carbonyl (PC) and advanced oxidation protein product (AOPP) as protein oxidation products (PPP) and antioxidants such as reduced glutathione (GSH),total thiol (TT) levels were analyzed in 25 patients with diagnosed pulmonary tuberculosis (TB) and 25 normal healthy age and sex matched controls. Statistically significant increased (p-0.001) levels of PC and AOPP were noted; GSH (p-0.013) and TT (p-0.001) levels were decreased .Hence increased oxidative stress signified by increased protein oxidation product and altered antioxidant levels may have a role in etiopathogenesis of pulmonary tuberculosis.